Clinical Application of Circulating Tumor Cells and Circulating Endothelial Cells in Predicting Bladder Cancer Prognosis and Neoadjuvant Chemosensitivity - Yang, Xiao; Lv, Jiancheng; Zhou, Zijian; Feng, Dexiang; Zhou, Rui; Yuan, Baorui; Wu, Qikai; Yu, Hao; Han, Jie; Cao, Qiang; Gu, Min; Li, Pengchao; et al. (Frontiers in Oncology, 2022)
PURPOSE: To investigate the role of circulating rare cells (CRCs), including circulating tumor cells (CTCs) and circulating endothelial cells (CECs), in aiding early intervention, treatment decision, and prognostication in bladder cancer. METHODS: 196 patients with pathologically confirmed bladder cancer including 141 non-muscle invasive bladder cancer (NMIBC) and 55 muscle invasive bladder cancer (MIBC) patients. There were 32 patients received cisplatin-based neoadjuvant chemotherapy (NAC) followed by radical cystectomy (RC). Subtraction enrichment combined with immunostaining-fluorescence in situ hybridisation (SE-iFISH) strategy was used for CTC/CEC detection. Kaplan–Meier analysis and cox regression were used to evaluate the overall survival (OS) and recurrence-free survival (RFS). Receiver operator characteristic analysis was used to discriminate NAC sensitivity. RESULTS: CTCs and CECs were related to clinicopathological characteristics. Triploid CTCs, tetraploid CTCs, and total CECs were found to be higher in incipient patients than in relapse patients (P=0.036, P=0.019, and P=0.025, respectively). The number of total CECs and large cell CECs were also associated with advanced tumor stage (P=0.028 and P=0.033) and grade (P=0.028 and P=0.041). Remarkably, tumor-biomarker-positive CTCs were associated with worse OS and RFS (P=0.026 and P=0.038) in NMIBC patients underwent TURBT. CECs cluster was an independent predictor of recurrence in non-high-risk NMIBC patients underwent TURBT (HR=9.21, P=0.040). For NAC analysis, pre-NAC tetraploid CTCs and small cell CTCs demonstrated the capability in discriminating NAC-sensitive from insensitive patients. Additionally, tetraploid CTCs and single CTCs elevated post-NAC would indicate chemoresistance. CONCLUSION: CTCs and CECs may putatively guide in diagnosis, prognosis prediction, and therapeutic decision-making for bladder cancer.